Извлечение воскоподобных веществ из отходов вымораживания подсолнечного масла с использованием реакции алкоголиза - Омельченко, Юлия Евгеньевна; Демидов, Игорь Николаевич (НТУ "ХПИ", 2016)
В статье представлены результаты исследования извлечения воскоподобных веществ из отработанного фильтрующего порошка (зажиренный перлит) с использованием реакции алкоголиза. Установлены рациональные условия процесса алкоголиза с использованием в качестве катализаторов алкилсульфокислоту и концентрированную серную кислоту. Показано, что использование данных катализаторов позволяет получить этиловые эфиры жирных кислот и максимально извлечь воскоподобные вещества без предварительной экстракции липидной части из отработанного фильтровального порошка.

The article presents the results of the extraction study waxen substances from the waste filter powder using alcoholysis reaction. Alcoholysis conditions set rational process using, as catalysts, alkylsulfonic and concentrated sulfuric acid in an amount of 4% and 3% respectively. The possibility of carrying out an alcoholysis reaction directly on the waste filter powder without prior extraction of the lipid portion. This simplifies the hardware design and eliminates the use of multiple solvents. The initial conditions for the alcoholysis were waste filter powder : absolute ethanol as 1:15. Yield of ethyl ester of fatty acids - biodiesel component was about 70%. Extracting identified possibility wax-like substances from the reaction mixture after the alcoholysis reaction, which was greater than 80% of the total amount of waxen substances in the lipid portion of the : waste filter powder.
Removing the waxen substances from waste freezing sunflower oil using alcoholysis reaction
Keywords: масложировая отрасль; фильтрующий порошок; рафинация; алкилсульфокислота; концентрированная серная кислота; waste filter powder; waxen substances; alcoholysis; alkylsulfonic acid; concentrated sulfuric acid